72.0k views
20 votes
If f(x) = 2x + 5x and g(x) = 3x - 5, find (f+ g)(x).

O A. 2X + 8x - 5
B. 2X + 2x + 5
C. 24 - 2x - 5
D. 10x - 5

User Georger
by
5.2k points

1 Answer

6 votes

Answer:

D. 10x - 5

General Formulas and Concepts:

Algebra I

  • Terms/Coefficients/Degrees

Explanation:

Step 1: Define

f(x) = 2x + 5x

g(x) = 3x - 5

(f + g)(x) is f(x) + g(x)

Step 2: Simplify

f(x) = 7x

g(x) = 3x - 5

Step 3: Find

  1. Substitute: (f + g)(x) = 7x + (3x - 5)
  2. Combine like terms: (f + g)(x) = 10x - 5
User Cfischer
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.